2017
DOI: 10.1007/s11897-017-0337-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation – Cause or Consequence of Heart Failure or Both?

Abstract: Purpose of ReviewWith the intention to summarize the currently available evidence on the pathophysiological relevance of inflammation in heart failure, this review addresses the question whether inflammation is a cause or consequence of heart failure, or both.Recent FindingsThis review discusses the diversity (sterile, para-inflammation, chronic inflammation) and sources of inflammation and gives an overview of how inflammation (local versus systemic) can trigger heart failure. On the other hand, the review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
297
0
14

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(317 citation statements)
references
References 180 publications
(218 reference statements)
6
297
0
14
Order By: Relevance
“…NT-proBNP is produced in response to cardiac stretch, 25 and experimental evidence has indeed demonstrated that stretched cardiomyocytes and cardiac fibroblasts elaborate TNF-/IL-6 and IL-1 , respectively. 19 This is also in agreement with the finding that elevated IL-6 levels are independently predicted by higher TNF-/IL-1 related biomarkers. PCT was an additional independent predictor of elevated IL-6 levels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…NT-proBNP is produced in response to cardiac stretch, 25 and experimental evidence has indeed demonstrated that stretched cardiomyocytes and cardiac fibroblasts elaborate TNF-/IL-6 and IL-1 , respectively. 19 This is also in agreement with the finding that elevated IL-6 levels are independently predicted by higher TNF-/IL-1 related biomarkers. PCT was an additional independent predictor of elevated IL-6 levels.…”
Section: Discussionsupporting
confidence: 91%
“…SERCA2 is involved in diastolic cardiomyocyte relaxation by mediating calcium reabsorption in the sarcoplasmic reticulum . Additionally, IL‐6 increases cardiomyocyte stiffness by reducing titin phosphorylation . These processes might in turn explain the association of IL‐6 with diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other antioxidants B2BrBC and C66 treatment did not prevent RV hypertrophy (Table ) and this might be related to a weak effect of the applied dosages on pulmonary arterial function . Increased ROS are associated with proinflammatory and profibrotic events in the pressure‐overloaded myocardium and also induce antioxidant enzymes by direct activation of transcription factors . These mechanisms could be responsible for the observed changes in the RV of the MCT group in our study (Figure ).…”
Section: Discussionsupporting
confidence: 58%
“…HF is a progressive condition in which cardiac muscle weakens and becomes inefficient to meet the body's demand for blood and oxygen supply. The etiology of HF is multifaceted as several genetic, biochemical, electrical and inflammatory factors have been shown to underlie the structural and functional remodeling that develops over time [5][6][7][8]. Based on the currently available literature, a majority of the HF conditions have been correlated with oxidative stress for the past several decades.…”
Section: Introductionmentioning
confidence: 99%